Atherectomy for peripheral arterial disease - Wardle, Bethany G; Ambler, Graeme K; Radwan, Rami W; Hinchliffe, Robert J; Twine, Christopher P (Cochrane database of systematic reviews, 2020)
Symptomatic peripheral arterial disease (PAD) has several treatment options, including angioplasty, stenting, exercise therapy, and bypass surgery. Atherectomy is an alternative procedure, in which atheroma is cut or ground away within the artery. This is the first update of a Cochrane Review published in 2014. To evaluate the effectiveness of atherectomy for peripheral arterial disease compared to other established treatments. The Cochrane Vascular Information Specialist searched the Cochrane Vascular Specialised Register, Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Allied and Complementary Medicine (AMED) databases, and the World Health Organization International Clinical Trials Registry Platform and ClinicalTrials.gov trials registers to 12 August 2019. We included all randomised controlled trials that compared atherectomy with other established treatments. All participants had symptomatic PAD with either claudication or critical limb ischaemia and evidence of lower limb arterial disease. Two review authors screened studies for inclusion, extracted data, assessed risk of bias and used GRADE criteria to assess the certainty of the evidence. We resolved any disagreements through discussion. Outcomes of interest were: primary patency (at six and 12 months), all-cause mortality, fatal and non-fatal cardiovascular events, initial technical failure rates, target vessel revascularisation rates (TVR; at six and 12 months); and complications. We included seven studies, with a total of 527 participants and 581 treated lesions. We found two comparisons: atherectomy versus balloon angioplasty (BA) and atherectomy versus BA with primary stenting. No studies compared atherectomy with bypass surgery. Overall, the evidence from this review was of very low certainty, due to a high risk of bias, imprecision and inconsistency. Six studies (372 participants, 427 treated lesions) compared atherectomy versus BA. We found no clear difference between atherectomy and BA for the primary outcomes: six-month primary patency rates (risk ratio (RR) 1.06, 95% confidence interval (CI) 0.94 to 1.20; 3 studies, 186 participants; very low-certainty evidence); 12-month primary patency rates (RR 1.20, 95% CI 0.78 to 1.84; 2 studies, 149 participants; very low-certainty evidence) or mortality rates (RR 0.50, 95% CI 0.10 to 2.66, 3 studies, 210 participants, very low-certainty evidence). One study reported cardiac failure and acute coronary syndrome as causes of death at 24 months but it was unclear which arm the participants belonged to, and one study reported no cardiovascular events. There was no clear difference when examining: initial technical failure rates (RR 0.48, 95% CI 0.22 to 1.08; 6 studies, 425 treated vessels; very low-certainty evidence), six-month TVR (RR 0.51, 95% CI 0.06 to 4.42; 2 studies, 136 treated vessels; very low-certainty evidence) or 12-month TVR (RR 0.59, 95% CI 0.25 to 1.42; 3 studies, 176 treated vessels; very low-certainty evidence). All six studies reported complication rates (RR 0.69, 95% CI 0.28 to 1.68; 6 studies, 387 participants; very low-certainty evidence) and embolisation events (RR 2.51, 95% CI 0.64 to 9.80; 6 studies, 387 participants; very low-certainty evidence). Atherectomy may be less likely to cause dissection (RR 0.28, 95% CI 0.14 to 0.54; 4 studies, 290 participants; very low-certainty evidence) and may be associated with a reduction in bailout stenting (RR 0.26, 95% CI 0.09 to 0.74; 4 studies, 315 treated vessels; very low-certainty evidence). Four studies reported amputation rates, with only one amputation event recorded in a BA participant. We used subgroup analysis to compare the effect of plain balloons/stents and drug-eluting balloons/stents, but did not detect any differences between the subgroups. One study (155 participants, 155 treated lesions) compared atherectomy versus BA and primary stenting, so comparison was extremely limited and subject to imprecision. This study did not report primary patency. The study reported one death (RR 0.38, 95% CI 0.04 to 3.23; 155 participants; very low-certainty evidence) and three complication events (RR 7.04, 95% CI 0.80 to 62.23; 155 participants; very low-certainty evidence) in a very small data set, making conclusions unreliable. We found no clear difference between the treatment arms in cardiovascular events (RR 0.38, 95% CI 0.04 to 3.23; 155 participants; very low-certainty evidence). This study found no initial technical failure events, and TVR rates at six and 24 months showed little difference between treatment arms (RR 2.27, 95% CI 0.95 to 5.46; 155 participants; very low-certainty evidence and RR 2.05, 95% CI 0.96 to 4.37; 155 participants; very low-certainty evidence, respectively). This review update shows that the evidence is very uncertain about the effect of atherectomy on patency, mortality and cardiovascular event rates compared to plain balloon angioplasty, with or without stenting. We detected no clear differences in initial technical failure rates or TVR, but there may be reduced dissection and bailout stenting after atherectomy although this is uncertain. Included studies were small, heterogenous and at high risk of bias. Larger studies powered to detect clinically meaningful, patient-centred outcomes are required.